Multidirectional sexual dimorphism for the live weight in domestic pigs - S. V. Nikitin; S. P. Knyazev; K. S. Shatokhin; G. M. Goncharenko; V. I. Ermolaуev (Вавиловский журнал генетики и селекции)
In mammals, males are typically larger and heavier than females. In particular, the average weight of wild boar females is about 80% of that of the males. In a vast majority of domestic swine populations (breeds, populations of breeding groups), this value varies from 70 to 91% (the central value of the range of variation of 81%). However, there are three genealogically continuous groups of domestic pigs (Vietnamese Masked breed MY, minisibs and Svetlogorsk mini-pigs) that make exceptions. Their specific feature is the reverse sexual dimorphism in weight – mature females are heavier than males. This phenomenon, not typical of the species Sus scrofa, was the reason for the present study. Although this research is preliminary, some assumptions can be made. Firstly, the ratio of the weight of mature females to the weight of mature males is obviously characteristic of the species, deviations from which repressed stabilizing selection. Second, in domestic pigs, normal and reverse sexual dimorphism in weight may be different in nature: in the former case, it is a great length of the period of intensive growth in males, in the latter, a large growth rate of females during the first year of life. The third characteristic of domestic pigs in Southeast Asia, early puberty, may be due to a consistent use of young and therefore small-sized males for reproduction purposes; however, the small size due to their youth, cannot be a target of artificial selection – nor can they be the cause of reverse sexual dimorphism in weight. Finally, reverse sexual dimorphism may be due to a tendency towards early obesity in females, which might be to a single mutation as its genetic cause.